Hindu law: beyond tradition and modernity - Menski, Werner (Oxford University Press, 2009)
This book analyses the development of Hindu law from the ancient period to its emergence as a postmodern phenomenon in the 21st century. The author uses comparative social theory literature to establish that Hindu law must be viewed both as an ancient, evolving conceptual entity and a living legal system.